2000
DOI: 10.1159/000057992
|View full text |Cite
|
Sign up to set email alerts
|

Self-Examination of Patients with Malignant Melanoma in the Aftercare: Relevance of Psychosocial Factors and Instructions by the Physicians

Abstract: Background: Several studies indicate that the prognosis of malignant melanoma (MM) can be improved if tumor progression, e.g. local recurrences and lymph node metastases, is detected at an early stage. Thus, instructed self-examination by the patients is recommended in aftercare. Although clinical experience shows that many patients do not sufficiently perform self-examination, no studies have so far focused on self-examination behavior. Objective: 1) To assess the self-examination behavior of patients with MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Not surprisingly, physician support plays a major role in improving SSE practices among melanoma patients. Patients who have been instructed by physicians on how to practice SSE conducted SSE significantly more often [58].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, physician support plays a major role in improving SSE practices among melanoma patients. Patients who have been instructed by physicians on how to practice SSE conducted SSE significantly more often [58].…”
Section: Discussionmentioning
confidence: 99%
“…Only a small proportion of people treated for melanoma perform regular total skin examination (a recent report estimated only 14%), but doing so may enable and empower individuals, with evidence that actively doing something to prevent recurrence or new primary melanoma offsets some of the worry . It is important that the effects of interventions to increase self‐examination on levels of melanoma‐associated fear are tested however, as overly frequent self‐examination may itself be associated with higher levels of anxiety (without randomized control trial evidence, it is difficult to know the direction of any possible causal relationship). Increased psychological support for people diagnosed with localised melanoma may be another way to decrease fear levels, as shown in a recent trial among high risk patients …”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of previous research is that key psychological variables, such as psychological distress, coping and professional/personal support, are widely neglected in relation to SSE. First, while distress is a very well known risk factor for non-compliance with medical advice in general [62-64], only few studies assessing SSE included a measure of psychological distress [65,66]. Second, while research has shown a higher prevalence of avoidant coping in skin cancer patients compared to both other cancer patients and healthy controls [67-72], only one study has examined the potential link between coping strategies and SSE in melanoma survivors [66].…”
Section: Introductionmentioning
confidence: 99%